Estratégias de ensino de leitura: um caminho para melhorar as aulas de leitura para os estudantes da EJA - Baliviera, Silvana de Castro Monteiro (2008)
This work is situated in the research line about Reading, Writing and Portuguese Language Teaching and has the purpose of contribute for the studies about the development of reading competence. Brazil didn t eradicate totally the analphabetism yet. Besides that, there is, today, another serious question: many young people and adults have the opportunity of studying, decode letters, phrases and short texts, but they have difficulties in constructing an interpretation of what they read; many times, they finish their course at EJA (Youth and Adult Education), without the basic competences required for being appropriately inserted in a society that is centered in the writing. The research verifies how the reading classes are given for young people and adults, if the teachers use strategies for teaching reading or not and if they were prepared to teach these people. The analyzed corpus is constituted by the answers given to a questionnaire, applied to teachers, of three neighbor schools, in São Paulo. The results show that most of teachers didn t have specialized formation to work with young people and adults, what contributes to the lack of identity of EJA, since the classes are basically the same that are prepared to the regular education. There is no special consideration for the specificity related to the age and to the culture of these students. Besides that, as the teachers didn t be prepared to teach how to read, they don t know the strategies for teaching reading and, in their classes, the reading is treated in a traditional way; the students read a text, without being motivated for the activity, without having objectives, so, the reading is frequently a grateful activity, without purpose. We suggest that teachers use the strategies for teaching reading as a way to the desired autonomy of young people and adult as lectors